Practice and factors affecting informed consent among healthcare workers for major surgical procedures at Gurage zone hospitals, South Ethiopia, 2022: a facility-based cross-sectional study - Haimanot Abebe; Bitew Tefera Zewudie; Yibeltal Mesfin; Shegaw Geze Tenaw; Daniel Tsega; Bogale Chekole; Zebene Mekonnen; Shegaw Tesfa Mengist; Agere Aynalem; Tadele Lankrew; Yihenew Sewale; Muche Argaw; et al. (BMJ Open)
Objective This study aimed to assess the informed consent practice process and associated factors among healthcare workers for major surgical procedures at Gurage zone hospitals, in 2022.Methods and materials Institution-based cross-sectional study was employed.Settings This study was conducted in Gurage zone hospitals.Participants All healthcare workers who have been working in Gurage zone hospitals of surgical, operation rooms and obstetrics/gynaecology wards had exposure to patients who had undergone surgery during the study periodOutcome The primary outcome of the study was the practice of informed consent practice among healthcare workers in Gurage zone hospitals.Result A total of 448 study participants were involved in this study giving a response rate of 98%. The mean (±SD) age of the study participants was 29.16 (±4.06) years. The mean score of study participants towards the surgical informed consent was 19.5, and 260 (58%, 95% CI: 53.7, 62.5) of them had good practice in the surgical informed consent. In multivariable logistic analysis model, factors like favourable attitude towards informed consent 2.4 (1.556, 3.596), work experience participants 4.9 (2.8, 8.7), adequate knowledge of informed consent 2.5 (1.6, 3.9) and communication challenge 1.6 (1.07, 2.50) were independently associated with the practice of informed consent at a p value of <0.05.Conclusion More than half of healthcare providers had good practice towards the surgical informed consent process. The practice of informed consent is low, and it is better to work on healthcare providers’ in-service training, knowledge and attitude towards informed consent.